“Anything That Can Prevent HIV Is Good”: Diverse Women Reflect on Potential Barriers, Facilitators, and Acceptability for PrEP - Kayla Etienne; Peyton R. Willie; Kimberly Lazarus; Ivanee Cruz; Valerie Daniel; Maria Silva Fernanda; Chelsie Warman; Gray Maganga; Bisola O. Ojikutu; Sannisha K. Dale (International Journal of Environmental Research and Public Health, 2026)
Introduction: Racially and ethnically diverse women experience sub-optimal outcomes on both the HIV treatment and prevention cascade when compared to their white counterparts due to factors including racism, sexism, and xenophobia. While PrEP is a promising biomedical tool that can narrow this gap, similar trends are observed in PrEP utilization among culturally diverse women. We sought to explore the differences in diverse women’s preferences, challenges, and facilitators of PrEP uptake. Methods: From January 2022 to July 2023, thirty-one diverse women who could benefit from PrEP in Miami, FL, completed qualitative interviews with trained research staff to discuss their willingness, perceptions, and access to PrEP. Women also completed a demographic survey via Research Electronic Data Capture (REDCap). Semi-structured interviews were analyzed via NVivo using a hybrid inductive–deductive thematic analysis approach. Results: The majority of participants were Black (81%) and ethnically diverse (41.9% African American, 25.8% Hispanic/Latina, 16.1% Afro-Caribbean Black (non-Haitian) and 16.1% Haitian/Haitian American). Qualitative coding revealed numerous themes common across ethnic groups on (a) HIV transmission risk, reasons for prevention, and protective factors, (b) PrEP awareness, acceptability and willingness, (c) access to healthcare, and (d) relationships. Conclusions: To develop culturally sound interventions to increase PrEP uptake among women most impacted by HIV, an understanding of their perspectives and experiences is needed, as well as interventions/strategies informed by their insights.